Effects of Climate Modes on Interannual Variability of Upwelling in the Tropical Indian Ocean - Zhang, Xiaolin; Han, Weiqing (Journal of climate, 2020)
This paper investigates interannual variability of the tropical Indian Ocean (IO) upwelling through analyzing satellite and in situ observations from 1993 to 2016 using the conventional Static Linear Regression Model (SLM) and Bayesian Dynamical Linear Model (DLM), and performing experiments using a linear ocean model. The analysis also extends back to 1979, using ocean–atmosphere reanalysis datasets. Strong interannual variability is observed over the mean upwelling zone of the Seychelles–Chagos thermocline ridge (SCTR) and in the seasonal upwelling area of the eastern tropical IO (EIO), with enhanced EIO upwelling accompanying weakened SCTR upwelling. Surface winds associated with El Niño–Southern Oscillation (ENSO) and the IO dipole (IOD) are the major drivers of upwelling variability. ENSO is more important than the IOD over the SCTR region, but they play comparable roles in the EIO. Upwelling anomalies generally intensify when positive IODs co-occur with El Niño events. For the 1979–2016 period, eastern Pacific (EP) El Niños overall have stronger impacts than central Pacific (CP) and the 2015/16 hybrid El Niño events, because EP El Niños are associated with stronger convection and surface wind anomalies over the IO; however, this relationship might change for a different interdecadal period. Rossby wave propagation has a strong impact on upwelling in the western basin, which causes errors in the SLM and DLM because neither can properly capture wave propagation. Remote forcing by equatorial winds is crucial for the EIO upwelling. While the first two baroclinic modes capture over 80%–90% of the upwelling variability, intermediate modes (3–8) are needed to fully represent IO upwelling.